2020
DOI: 10.1111/jphp.13343
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of non-steroidal anti-inflammatory drug-induced, ER stress-mediated apoptosis in Caco-2 cells by different polyphenolic antioxidants: a mechanistic study

Abstract: Objectives Direct scavenging of reactive oxygen species could not prevent ER stress-associated cytotoxicity of indomethacin or diclofenac in Caco-2 cells. This study investigated the effects of three polyphenolic antioxidants epigallocatechin gallate (EGCG), phyllanthin and hypophyllathin in non-steroidal anti-inflammatory drug-induced Caco-2 apoptosis. Methods Cells were treated with ER stressors (indomethacin, diclofenac, tunicamycin or thapsigargin) and the polyphenols for up to 72 h. Cell viability, apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…PERK (PEK-1 in C. elegans), the second ER stress sensor, is an ER transmembrane protein [27]. In a cellular model, EGCG inhibited the expression of the ER stress marker ATF4 in trabecular meshwork cells treated with Tm [39], suppressed the increase in p-PERK/p-eIF-2α/ATF-4 expression levels in Caco-2 cells treated with Tm and thapsigargin [40], and decreased the expression of p-PERK in high-glucose-induced podocytes [41]. Our study shows that RNAi targeting pek-1 abolishes the inhibitory effect of EGCG on Cd-induced ER stress in the nematode head (Figure 5A,B).…”
Section: Discussionmentioning
confidence: 99%
“…PERK (PEK-1 in C. elegans), the second ER stress sensor, is an ER transmembrane protein [27]. In a cellular model, EGCG inhibited the expression of the ER stress marker ATF4 in trabecular meshwork cells treated with Tm [39], suppressed the increase in p-PERK/p-eIF-2α/ATF-4 expression levels in Caco-2 cells treated with Tm and thapsigargin [40], and decreased the expression of p-PERK in high-glucose-induced podocytes [41]. Our study shows that RNAi targeting pek-1 abolishes the inhibitory effect of EGCG on Cd-induced ER stress in the nematode head (Figure 5A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant evidence has revealed the transcriptional programs of these transporters are largely regulated by HIF-1α, ATF4, and Myc ( 198 , 199 ). Indeed, it has been observed that EGCG can markedly reduce the expression of these transcription factors in tumors ( 16 , 200 , 201 ). Given that, we speculate EGCG may downregulate the expression levels of the abovementioned glutamine receptors, but direct experimental results are still needed to confirm our hypothesis.…”
Section: Regulatory Roles In Tumor Metabolic Reprogrammingmentioning
confidence: 99%
“…Its notable adverse effect has been related to gastrointestinal damage which, in part, occurs from its inhibition against mitochondrial complex I activity and production of stress-induced apoptotic cell death [1] , [2] , [3] . Recently, we demonstrated that some natural antioxidants with ability to suppress endoplasmic reticulum (ER) stress such as epigallocatechin, quercetin and rutin could prevent diclofenac-induced apoptosis in Caco-2 cell, which is a widely accepted cell model for intestinal absorption, as well as in intestinal rat tissue [4] , [5] . Their “key” protective mechanisms involve inhibition of PERK-CHOP ER sensor activation, and maintaining mitochondrial permeability and function [4] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, certain antioxidants such as phyllanthin and silymarin increased diclofenac toxicity in Caco-2 cells through suppression of survival responses and/ or increase of apoptosis [5] . For example, the potentiation effect of phyllanthin was caused by downregulating the expression of p-Nrf-2/HO-1 proteins, activating PERK-CHOP proteins, disrupting mitochondrial membrane permeability (MMP), and inducing apoptosis [4] . Silymarin, a known hepatoprotective compound in milk thistle, enhanced apoptosis of diclofenac-treated Caco-2 cells possible through MMP disruption without generating ER stress [5] .…”
Section: Introductionmentioning
confidence: 99%